2015
DOI: 10.1007/s10639-015-9409-1
|View full text |Cite
|
Sign up to set email alerts
|

VLEs, social stories and children with autism: A prototype implementation and evaluation

Abstract: Virtual Learning Environments (VLEs) have been successfully used in educational interventions for children with Autism Spectrum Conditions (ASC) for overcoming their persistent differences related to social communication and imagination. This paper investigates the potential of VLEs presenting Social Stories, as an advantageous pathway for the development of social problem skills in children with ASC. To this end, it presents the design and development of VLSS (Virtual Learning Environment with Social Stories)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Volioti et al . (2016) asked special education teachers their views on an application teaching social skills to children with autism via social stories. The teachers responded for themselves but also on behalf of students with autism and reported that the application was easy to use and they also expressed high levels of satisfaction.…”
Section: Resultsmentioning
confidence: 99%
“…Volioti et al . (2016) asked special education teachers their views on an application teaching social skills to children with autism via social stories. The teachers responded for themselves but also on behalf of students with autism and reported that the application was easy to use and they also expressed high levels of satisfaction.…”
Section: Resultsmentioning
confidence: 99%
“…The scenario was also inspired from the novel "Social Stories" techniques in use by a number of autism-related VR solutions, which further justifies our approach [17]. The "greeting" scenario, a general situation that an average indi-vidual faces multiple times per day, can help to track the user's level of social interaction with multiple usages of the VR system.…”
Section: Social Communication Task Modulementioning
confidence: 88%
“…Social cues can be simulated virtually to enhance learning environments in ways that are impossible in real life; for example, Bailenson et al (2005) studied "augmented gaze," which simulated optimal teacher eye contact and gaze with multiple students simultaneously and gave each participant the best seat location in a virtual classroom, leading to improved learning. Various socio-emotional learning opportunities are also possible, such as teaching social perception skills and emotion recognition for students with autism spectrum disorder (e.g., Volioti et al, 2016). Furthermore, social XR platforms can be designed to support connectivist approaches (e.g.…”
Section: High Consideration Of Educational Efficacymentioning
confidence: 99%